Evaluation of research on interventions aligned to WHO 'Best Buys' for NCDs in low-income and lower-middle-income countries: a systematic review from 1990 to 2015. Issue 1 (19th February 2018) - Allen, Luke N; Pullar, Jessica; Wickramasinghe, Kremlin Khamarj; Williams, Julianne; Roberts, Nia; Mikkelsen, Bente; Varghese, Cherian; Townsend, Nick
Abstract : Background: Non-communicable diseases (NCDs) are the leading cause of death and disability worldwide, with low-income and middle-income countries experiencing a disproportionately high burden. Since 2010 WHO has promoted 24 highly cost-effective interventions for NCDs, dubbed 'best buys'. It is unclear whether these interventions have been evaluated in low-income and lower-middle-income countries (LLMICs). Aim: To systematically review research on interventions aligned to WHO 'best buys' for NCDs in LLMICs. Methods: We searched 13 major databases and included papers conducted in the 83 World Bank-defined LLMICs, published between 1 January 1990 and 5 February 2015. Two reviewers independently screened papers and assessed risk of bias. We adopted a narrative approach to data synthesis. The primary outcomes were NCD-related mortality and morbidity, and risk factor prevalence. Results: We identified 2672 records, of which 36 were included (608 940 participants). No studies on 'best buys' were found in 89% of LLMICs. Nineteen of the 36 studies reported on the effectiveness of tobacco-related 'best buys', presenting good evidence for group interventions in reducing tobacco use but weaker evidence for interventions targeting individuals. There were fewer studies on smoking bans, warning labels and mass media campaigns, and no studies on taxes or marketing restrictions. There was supportive evidence that cervical screening and hepatitis B immunisation prevent cancer in LLMICs. A single randomised controlled trial supported polypharmacy for cardiovascular disease. Fourteen of the 'best buy' interventions did not have any good evidence for effectiveness in LLMICs. Conclusions: We found studies on only 11 of the 24 interventions aligned with the WHO 'best buys' from LLMIC settings. Most LLMICs have not conducted research on these interventions in their populations. LLMICs should take action to implement and evaluate 'best buys' in their national context, based on national priorities, and starting with interventions with the strongest evidence base.